Dual activation: coupling ultrasound to electrochemistry - an overview - Compton, R; Eklund, J; Marken, F; Rebbitt, T; Akkermans, R; Waller, D (Elsevier, 1997)
By introducing a powerful immersion horn probe as a source of intense ultrasound into a thermostatted conventional three-electrode cell, dual activation experiments by simultaneously passing a current and applying ultrasound may be undertaken. These sono-voltammetric experiments may be used in order to analyse and quantify the processes induced by ultrasound at the electrode/solution interface. Different effects have been described. First, by applying intense sound fields direct effects of ultrasound on electrode surfaces such as depassivation and erosion can be induced in cavitation events, violent collapses of oscillating bubbles. Second, the huge effect of ultrasound on the mass transport at the electrode surface detected by various voltammetric techniques may be described by the model of an extremely thinned diffusion layer of uniform accessibility. This experimentally verified model may then be used in voltammetric experiments in order to separate pure mass transport from other effects induced by sound waves. Several working electrode geometries have been employed and particularly the use of an electrode embedded in the tip of the ultrasound transducer, a so-called sonotrode, allows extreme conditions to be studied. In aqueous media and under these conditions voltammetry parallel to "classical" hydrodynamic techniques based on the effect of "acoustic streaming" was observed. A wide range of systems including the reduction of a metalloprotein, cytochrome c, are described. In this overview the current state-of-the-art is critically reviewed and the information that has been derived from sonovoltammetric measurements illustrated. © 1997 Elsevier Science Ltd.